Constructing a Peaceful Imperialism: Manipulating Gender Identity in the Comentarios reales de los Incas - Heid, Patricia (The sixteenth century journal, 2002)
The Inca Garcilaso de la Vega was the first mixed-blood, or mestizo, author to publish in Spanish. In his 1609 Comentarios reales de los Incas (Royal commentaries of the Incas), he describes the Incas' extended campaign of conquest and colonization of the other so-called barbarous indigenous groups of Peru. The Comentarios depicts the Incas as exemplary conquerors, who practiced an ideology of peaceful imperialism, characterized by constant dialogue and interaction with their conquered subjects. This ideology contrasted with the dominant ideology of Spanish histories, based on the epic model. Garcilaso specifically manipulates the binary paradigm of gender identities inherent in epic, which legitimizes conquest by force as the natural dominance of a male-gendered, civilized conqueror over a female-gendered, barbarian subject. Garcilaso took as his model the paradigm of gender relations elaborated by Leone Ebreo in his treatise on Neoplatonic love, the Dialoghi d'amore, which Garcilaso had translated into Spanish and published in 1590.